ON THE GAME PROBLEM OF CONTROLLING A STACK OF TRAJECTORIES IN DELAY EQUATIONS - Bekzod M. Tokhirov (International Scientific and Current Research Conferences, 2022)
This article deals with the game problem of controlling a stack of trajectories in delay equations. When solving a system of equations and variables are given in plural form, i.e. in parentheses. Results are also plural. The assign function is used to make them look normal. It assigns the values from the array (within the curly braces) to the variables.